2020
DOI: 10.1007/s13300-020-00962-3
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide Reduces Carotid Intima-Media Thickness by Reducing Small Dense Low-Density Lipoproteins in a Real-World Setting of Patients with Type 2 Diabetes: A Novel Anti-Atherogenic Effect

Abstract: Introduction Liraglutide has several non-glycemic effects, including those on plasma lipids and lipoproteins, contributing to its cardiovascular benefit; however, the exact underlying mechanisms remain unclear. We investigated a novel anti-atherogenic effect of liraglutide in a real-world prospective study on patients with type 2 diabetes (T2DM). Methods Sixty-two patients with T2DM (31 men, 31 women; mean age ± standard deviation 61 ± 9 years) naïve to incretin-based t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 43 publications
3
34
0
Order By: Relevance
“…It has been hypothesized that the underlying mechanism of this beneficial GLP-1 RA effect is an preventive effect of GLP-1 RAs on atherosclerotic plaque formation 7 and/or anti-inflammatory actions of GLP-1 RAs. Hence, clinical studies have suggested that GLP-1 RA treatment reduces small dense low-density lipoproteins 8 , carotid-intima media thickness 8 , 9 , specific microRNAs involved in vascular inflammation and cardiovascular metabolism 10 , oxidative stress 11 and circulating inflammatory markers 12 – 14 . The inflammatory markers reduced by GLP-1 RA in clinical studies in humans, include circulating plasma levels of tumor necrosis factor (TNF)-α 15 , interleukin (IL)-1β, IL-6 and cluster of differentiation 163 (CD163) 16 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesized that the underlying mechanism of this beneficial GLP-1 RA effect is an preventive effect of GLP-1 RAs on atherosclerotic plaque formation 7 and/or anti-inflammatory actions of GLP-1 RAs. Hence, clinical studies have suggested that GLP-1 RA treatment reduces small dense low-density lipoproteins 8 , carotid-intima media thickness 8 , 9 , specific microRNAs involved in vascular inflammation and cardiovascular metabolism 10 , oxidative stress 11 and circulating inflammatory markers 12 – 14 . The inflammatory markers reduced by GLP-1 RA in clinical studies in humans, include circulating plasma levels of tumor necrosis factor (TNF)-α 15 , interleukin (IL)-1β, IL-6 and cluster of differentiation 163 (CD163) 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Liraglutide and semaglutide significantly attenuated plaque lesion development in Apolipoprotein E (ApoE)−/− and LDL-R−/−) deficient mice; semaglutide treatment improved leukocyte recruitment, leukocyte rolling, adhesion/extravasation, cholesterol metabolism, lipid-mediated signaling, extracellular matrix protein turnover, and plaque hemorrhage [ 66 ]. Liraglutide improves metabolic parameters and carotid intima-media thickness in diabetic patients with the metabolic syndrome [ 67 ] and, very recently, it has been shown a novel anti-atherogenic effect of liraglutide in patients with type-2 diabetes: the decrease in subclinical atherosclerosis by a reduction in atherogenic small, dense LDL particles [ 68 ]. Semaglutide treatment significantly lowered fasting and postprandial lipid metabolism vs. placebo [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…On this basis, GLP1-RAs are now clearly identified by scientific guidelines as a treatment of choice for T2DM; yet, the adoption of such international recommendations is still suboptimal, and this contributes negatively to what we perceive as clinical inertia [24,25]. Since atherosclerotic CVD is predominant in T2DM patients, it should be also considered that some GLP1-RAs, such as liraglutide and semaglutide, have shown direct antiatherosclerotic effects that help explaining the beneficial cardiovascular outcomes [26][27][28]. Some interesting novel findings have been discussed during the recent 81st Annual Scientific Sessions of the American Diabetes Association where, for instance, the data on efficacy, safety, and tolerability of the dual GIP and GLP-1 receptor agonist tirzepatide were presented.…”
mentioning
confidence: 99%